A comparison of the therapeutic efficacies of large loop excision of the transformation zone and hysterectomy for the treatment of cervical intraepithelial neoplasia III. Issue 5 (1st September 2001) - Kang, S.-B.; Roh, J.-W.; Kim, J.-W.; Park, N.-H.; Song, Y.-S.; Lee, H.-P.
Abstract : The technique of large loop excision of the transformation zone (LLETZ) came into vogue in the 1990s, and has been widely used in place of cold knife conization for diagnosis and treatment. Although its therapeutic efficacy for cervical intraepithelial neoplasia (CIN) has been confirmed and accepted in many countries, no direct comparison is available of the efficacies of LLETZ and hysterectomy for the treatment of CIN III, and unfortunately, hysterectomy is still widely used in many other countries. The aim of this analysis was to confirm the efficacy of LLETZ for the treatment of CIN III and to compare its results with those of hysterectomy. Between Jan. 1993 and De c . 1997, 380 patients with CIN III were treated in the Seoul National University Hospital. We defined group I ( n = 101) as those patients who underwent therapeutic LLETZ and follow-up only and group II ( n = 279) as those patients who underwent hysterectomy following LLETZ. Three patients in groups I (3.0%) and II (1.1%) developed persistent/recurrent CIN or vaginal intraepithelial neoplasia (VAIN). This result was not statistically significant. Group II contained more patients with positive resection margins and glandular extensions than group I ( P < 0.05), and these factors might have been confounding variables. However, when parameters influencing the rate of treatment failure were compared, no significant differences were found by logistic regression analysis ( P > 0.05). The results obtained show that the LLETZ is almost identical in terms of its therapeutic efficacy to hysterectomy and that it should be accepted as a standard treatment for CIN III.